2003
DOI: 10.1038/nature01236
|View full text |Cite
|
Sign up to set email alerts
|

Larval stages of a living sea lily (stalked crinoid echinoderm)

Abstract: The embryos and larvae of stalked crinoids, which are considered the most basal group of extant echinoderms, have not previously been described. In contrast, much is known about the development of the more accessible stalkless crinoids (feather stars), which are phylogenetically derived from stalked forms. Here we describe the development of a sea lily from fertilization to larval settlement. There are two successive larval stages: the first is a non-feeding auricularia stage with partly longitudinal ciliary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
104
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 3 publications
1
104
0
Order By: Relevance
“…This hypothesis would be further supported if one could show, for example, an ontogenetic transformation of a single circum-blastoporal ciliary band into two transverse ciliary bands of the pilidium nielseni. Ontogenetic re-arrangement of a single larval ciliary band or a uniform ciliary field into several transverse rings has been shown in holothuroid and crinoid echinoderms (Lacalli andWest 1986, 2000;Nakano et al, 2003). Perhaps, spiralians are not immune to such developmental or evolutionary transformations either.…”
Section: B C D a 590 Sa Maslakova And Tc Hiebertmentioning
confidence: 99%
“…This hypothesis would be further supported if one could show, for example, an ontogenetic transformation of a single circum-blastoporal ciliary band into two transverse ciliary bands of the pilidium nielseni. Ontogenetic re-arrangement of a single larval ciliary band or a uniform ciliary field into several transverse rings has been shown in holothuroid and crinoid echinoderms (Lacalli andWest 1986, 2000;Nakano et al, 2003). Perhaps, spiralians are not immune to such developmental or evolutionary transformations either.…”
Section: B C D a 590 Sa Maslakova And Tc Hiebertmentioning
confidence: 99%
“…In ophiuroid and echinoid echinoderms, a pluteus larva develops that has an oral-aboral axis, but the second axis is not exactly anteriorposterior and so is referred to as the A-V (Angerer et al 2001). However, in other echinoderm larvae, including basal crinoid larvae, it is clear that the egg A-V axis becomes the larval A-P axis (Nakano et al 2003). In hemichordates, the adult A-P axis is clearly identical to the larval A-P axis and the D-V axis is still being debated (Gerhart, 2001;Henry et al, 2001).…”
Section: Deuterostome Gastrulationmentioning
confidence: 99%
“…They showed that the gene expression domains of hemichordates and chordates are surprisingly conserved, an observation that shed new light on the evolution of the central nervous system and the phyletic placement of chordates. In echinoderms, Nakano et al (2003) described the development of the sea lily, Metacrinus rotundus , and reported that this most basal echinoderm develops via a dipleurula-type larva. This observation strongly suggests that the latest common ancestor of echinoderms and hemichordates may be an indirect developer with dipleurula-type larvae, and Nakano et al (2003) have suggested that the common ancestor of deuterostomes (including chordates) may be an indirect developer.…”
Section: B Misakiensis As a Model Organismmentioning
confidence: 99%